Delivering Opportunistic Behavior Change Interventions: a Systematic Review of Systematic Reviews - Keyworth, Chris (Prev Sci, 2020)
Opportunities for healthcare professionals to deliver health behavior change interventions are often missed, but understanding the barriers and enablers to this activity is limited by a focus on defined specialisms/health conditions. This systematic review of systematic reviews collates all the evidence across professional groups to provide guidance to policy makers for implementing healthcare professional delivery of behavior change interventions. Eight electronic databases were searched for systematic reviews reporting patient-facing healthcare professionals’ (e.g., general practitioners, nurses) barriers and enablers to delivering behavior change interventions (diet, physical activity, alcohol reduction, smoking cessation, and weight management). A narrative synthesis was conducted. Thirty-six systematic reviews were included. Four themes emerged as both barriers and enablers: (1) perceptions of the knowledge or skills needed to support behavior change with patients, (2) perceptions of the healthcare professional role, (3) beliefs about resources and support needed, and (4) healthcare professionals’ own health behavior. There were four cross-disciplinary barriers: (1) perceived lack of time, (2) perceived lack of prioritization of health behavior change, (3) negative attitudes towards patients and perceptions of patient risk, and (4) perceptions of patient motivation. The three enablers were as follows: (1) training, (2) context, and (3) attitudes towards delivering interventions. To enhance healthcare professionals’ delivery of behavior change interventions, policy makers should (a) address perceptions about patient need for interventions, (b) support diverse professional groups to identify opportunities to deliver interventions, and (c) encourage professionals to focus on prevention and management of health conditions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11121-020-01087-6) contains supplementary material, which is available to authorized users.